2011
DOI: 10.1080/02773813.2010.550379
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sugarcane Bagasse Lignin S/G/H Ratio by Pyrolysis GC/MS

Abstract: In this work, analytical pyrolysis (Py-GC-MS) was employed to identify lignin markers derived from H, S, and G phenylpropanoid units in sugarcane bagasse. Temperatures of 450 and 500 • C allowed the detection of key products that were informative on the bagasse lignin composition. The method was validated by comparing the S/G ratio as determined by the nitrobenzene oxidation (NBO) standard method for five sugarcane varieties. The S/G ratio as determined by Py-GC-MS, taking into consideration all known lignin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
1
29
1
Order By: Relevance
“…The values for lignin content presented in our study are significantly lower than those previously reported for sugarcane bagasse (Lopes et al, 2011;Masarin et al, 2011;Rezende et al, 2011). Sugarcane bagasse is the residue produced after Suc extraction and is composed of 39% cellulose, 25% hemicelluloses, and 23% lignin, among other minor components (Carroll and Somerville, 2009).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The values for lignin content presented in our study are significantly lower than those previously reported for sugarcane bagasse (Lopes et al, 2011;Masarin et al, 2011;Rezende et al, 2011). Sugarcane bagasse is the residue produced after Suc extraction and is composed of 39% cellulose, 25% hemicelluloses, and 23% lignin, among other minor components (Carroll and Somerville, 2009).…”
Section: Discussioncontrasting
confidence: 77%
“…Here, only the internode, the region between two adjacent nodes, was used for lignin determination, while the highly lignified and fibrous nodes were discarded. Therefore, the high lignin values previously reported for sugarcane bagasse (Lopes et al, 2011;Masarin et al, 2011;Rezende et al, 2011) reflect the lignin content of a mixture of internodes and nodes and, therefore, cannot be directly compared with the values obtained here.…”
Section: Discussionmentioning
confidence: 57%
“…Thermochemical evaluations of lignin monomers have become increasing prevalent [4,5,13,59,[61][62][63][64][65][66]68,70,126,157,159,183,240,242,293,295,[298][299][300][301]303,305,306,308]. When heated, lignin linkages are cleaved, permitting the identification of individual monomeric moieties.…”
Section: Pyrolysismentioning
confidence: 99%
“…S/G lignin ratios have proven to be important parameters for gauging the recalcitrance of lignin, although no clear trend has been established as to whether or not a high S content results in increased monomeric sugar release following an enzymatic hydrolysis. The traditional methods for measuring lignin monomer composition include NMR, pyGCMS, pyMBMS, and various wet chemical methods such as nitrobenzene oxidation (NBO) and thioacidolysis [4,5,13,56,58,59,[61][62][63][64][65][66]68,70,126,135,157,159,183,240,242,[291][292][293][294][295][296][297][298][299][300][301][302][303][304][305][306][307]. Common pyrolysis and mass spectral fragments are listed in Table 8, and illustrated in Fig.…”
Section: Lignin Monomer Compositionmentioning
confidence: 99%
“…Lignin is usually described by the relative abundance and ratio of the H-, G-, and S-units (Campbell & Sederoff 1996). With some notable exceptions lignins from gymnosperms are composed of G-units only (with minor amounts of H-units), whereas grass lignins, including that from sugarcane (He & Terashima 1991;Lopes et al 2011), comprise mostly S-and G-units, with H-units much less abundant. Lignins in many crops may be acylated with different organic acids (Ralph et al 2004), but the biochemistry and functions of lignin acylation have not been elucidated.…”
Section: Lignin Compositionmentioning
confidence: 99%